Guidelines for Foreign Exchange Reserve Management. (Manuals and Guides, 2004)
These guidelines are intended to assist countries in strengthening their policy frameworks for reserve management so that they can become more resilient to shocks that may originate from global financial markets or within the domestic financial system. The guidelines have been developed as part of a broader IMF work program to help strengthen international financial architecture, to promote policies and practices that contribute to stability and transparency in the financial sector, and to reduce external vulnerabilities of member countries.